Letter from Edward N. Kent to James Curtis Booth, October 11, 1854 - Kent, Edward (1854)
Edward N. Kent of the United States Assay Office at New York informs James Curtis Booth (1810-1888) of the start-up of the New York assay operations.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; United States. Assay Office, New York City